Stock Valuation Before and After the COVID-19 Pandemic: Free Cash Flow to Firm (FCFF) and Relative Valuation Approach with Discounted Cash Flow (DCF) Valuation Method - Virta Dimas Catur Diputra; Brady Rikumahu (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study compares the valuation of hospital companies in the healthcare sector in Indonesia before and during the Covid-19 pandemic on the Indonesia Stock Exchange (IDX). Global crises, including the Covid-19 pandemic, have had a significant impact on stock prices in the IDX and have affected company valuations. Therefore, it is important to study the valuation of stocks in the healthcare sector, prices in the IDX and have affected company valuations. Therefore, it is important to study the valuation of stocks in the healthcare sector, especially in hospital companies that are directly related to the pandemic. This research is expected to provide important lessons about stock valuation in the future if a similar phenomenon occurs Methodology/approach: This research focuses on the period before Covid-19 and the period during the peak of Covid-19, specifically in July 2021. This study compared the stock valuations of three hospital companies: HEAL, MIKA, and SILO. The valuation methods used are Discounted Cash Flow using the Free Cash Flow to Firm model and Relative Valuation using PBV and PER. Results/findings: From the research results, it is known that there has been an increase in the intrinsic value (value per share) of SILO, MIKA, and HEAL from the period before Covid-19 and after the peak of Covid-19 in either pessimistic, moderate, and optimistic scenarios. This increase in intrinsic value is followed by an increase in share prices. MIKA’s valuation did not change in the three scenarios, whereas SILO and HEAL changed only in moderate scenarios. In the relative valuation analysis, there was an increase in PER for SILO, HEAL, and MIKA before and after the peak of Covid-19. Conclusions: The pandemic positively influenced the valuation of hospital stocks, driven by increased demand for healthcare services. This reflects the defensive nature of healthcare investments during crises. Limitations: The study is limited to three issuers and does not account for long-term post-pandemic effects or macroeconomic variables. Contribution: This research provides insights for investors and policymakers on how healthcare sector valuations behave during global health emergencies and offers a valuation framework for future crises.